Plankton community structure in response to hydrothermal iron inputs along the Tonga-Kermadec arc - Mériguet, Zoé; Vilain, Marion; Baudena, Alberto; Tilliette, Chloé; Habasque, Jérémie; Lebourges-Dhaussy, Anne; Bhairy, Nagib; Guieu, Cécile; Bonnet, Sophie; Lombard, Fabien (Frontiers in Marine Science, 2023)
The Western Tropical South Pacific (WTSP) basin has been identified as a hotspot of atmospheric dinitrogen fixation due to the high dissolved iron ([DFe]) concentrations (up to 66 nM) in the photic layer linked with the release of shallow hydrothermal fluids along the Tonga-Kermadec arc. Yet, the effect of such hydrothermal fluids in structuring the plankton community remains poorly studied. During the TONGA cruise (November-December 2019), we collected micro- (20-200 μm) and meso-plankton (>200 μm) samples in the photic layer (0-200 m) along a west to east zonal transect crossing the Tonga volcanic arc, in particular two volcanoes associated with shallow hydrothermal vents (< 500 m) in the Lau Basin, and both sides of the arc represented by Melanesian waters and the South Pacific Gyre. Samples were analyzed by quantitative imaging (FlowCam and ZooScan) and then coupled with acoustic observations, allowing us to study the potential transfer of phytoplankton blooms to higher planktonic trophic levels. We show that micro- and meso-plankton exhibit high abundances and biomasses in the Lau Basin and, to some extent, in Melanesian waters, suggesting that shallow hydrothermal inputs sustain the planktonic food web, creating productive waters in this otherwise oligotrophic region. In terms of planktonic community structure, we identified major changes with high [DFe] inputs, promoting the development of a low diversity planktonic community dominated by diazotrophic cyanobacteria. Furthermore, in order to quantify the effect of the shallow hydrothermal vents on chlorophyll a concentrations, we used Lagrangian dispersal models. We show that chlorophyll a concentrations were significantly higher inside the Lagrangian plume, which came into contact with the two hydrothermal sites, confirming the profound impact of shallow hydrothermal vents on plankton production.